1998
DOI: 10.1038/sj.onc.1202095
|View full text |Cite
|
Sign up to set email alerts
|

Spi-1 transgenic mice develop a clonal erythroleukemia which does not depend on p53 mutation

Abstract: Spi-1 transcriptional activation and wild-type p53 extinction are two oncogenic alterations involved in the malignant transformation of erythroblasts during the Friend acute erythroleukemia. To dissect the contribution of these alterations in the deregulation of the di erentiation and proliferation of erythroblasts, we generated spi-1 transgenic mice. Analysis of these animals revealed that Spi-1 overexpression was directly involved in the block of proerythroblast di erentiation. However, the erythroleukemia t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…We already reported that the Jak2/STAT5 pathway was at rest in HS2 cells as a direct consequence of an inactive EpoR, 26 excluding that anomalies in this pathway could lead to a proliferative signal in the HS2 cells. PI3K is involved in the regulation of many signaling events involved in mitogenesis and apoptosis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We already reported that the Jak2/STAT5 pathway was at rest in HS2 cells as a direct consequence of an inactive EpoR, 26 excluding that anomalies in this pathway could lead to a proliferative signal in the HS2 cells. PI3K is involved in the regulation of many signaling events involved in mitogenesis and apoptosis.…”
Section: Discussionmentioning
confidence: 91%
“…26 Then, we focused on other signaling pathways regulated by Epo in erythroid cells. First, we examined the contribution of PI3K to the survival and proliferation of HS1 and HS2 cells by analyzing the effect of the PI3K inhibitor LY294002 27 on cell growth ( Figure 2A).…”
Section: Pi3k Pathway Is Involved In Hs1 and Hs2 Cell Proliferationmentioning
confidence: 99%
“…In agreement with this result, a previous study has demonstrated that overexpression of Spi-1 in a transgenic mouse model blocks differentiation and induces Epo-dependent proliferation of erythroblasts. 40 Thus, high Spi-1 expression and low p27 expression in HB60-5 cells may be responsible for the block in differentiation in these cells. Since Spi-1 up-regulation was observed only in HB60-5 cells, perhaps the function of the mir-17-92 Posttranscriptional regulation of p27 by mir-17-92 cluster through a specific binding to the p27 3ЈUTR was examined using luciferase assay.…”
Section: Discussionmentioning
confidence: 99%
“…Direct evidence for deregulated expression of SPI-1/PU.1 in leukemogenesis was provided by the spontaneous development of multistep erythroleukemia in SPI-1 transgenic mice (4,5,44). SPI-1/PU.1 overexpression is involved in both the survival and the inhibition of differentiation of erythroid cells (47).…”
mentioning
confidence: 99%